O‐linked protein glycosylation in mycoplasma. Issue 5 (18th October 2013) - Jordan, David S.; Daubenspeck, James M.; Laube, Audra H.; Renfrow, Matthew B.; Dybvig, Kevin
Summary Although mycoplasmas have a paucity of glycosyltransferases and nucleotidyltransferases recognizable by bioinformatics, these bacteria are known to produce polysaccharides and glycolipids. We show here that mycoplasmas also produce glycoproteins and hence have glycomes more complex than previously realized. Proteins from several species of Mycoplasma reacted with a glycoprotein stain, and the murine pathogen Mycoplasma arthritidis was chosen for further study. The presence of M. arthritidis glycoproteins was confirmed by high‐resolution mass spectrometry. O‐linked glycosylation was clearly identified at both serine and threonine residues. No consensus amino acid sequence was evident for the glycosylation sites of the glycoproteins. A single hexose was identified as the O‐linked modification, and glucose was inferred by 13C‐labelling to be the hexose at several of the glycosylation sites. This is the first study to conclusively identify sites of protein glycosylation in any of the mollicutes.